Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Dinas Kependudukan Dan Pencatatan Sipil (Dukcapil) Kabupaten Seluma - Kamelia Astuty; Risna Purnama Sari; Kimas Kurniawan (UNIVED Press, 2023)
The purpose of this study was to determine the effect of tangible, reliability, responsiveness, assurance and empathy of service quality to consumer satisfaction of Dinas DUKCAPIL Seluma. The sampling technique in this study using purposive sampling techniques and data collection is done by distributing questionnaires to the respondents. The questionaires were distributed to the 100 respondent of Dinas DUKCAPIL Seluma. The analysis tool used is multiple linear regression using SPSS 16. Hypothesis testing using the T test. Result shows that partially, tangible, reliability, responsiveness, assurance and empathy variables has significant effect on consumer satisfaction of Dinas DUKCAPIL Seluma. Based on the analysis of known coefficient of determination value of Adjusted R Square is 0.477, this means 47,7% variable consumer satisfaction is influenced by variables service quality.